Landfill in Jasło – slope stability analysis with variable cohesion values for municipal waste - Mariusz Cholewa (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The paper presents results of tests and calculations aiming at the determination of the influence of changes in the values of municipal waste cohesion on the values of safety factor calculated with the Fellenius method. The works in questions were performed for the landfill for waste other than hazardous and inert waste located in Jasło.